2011
DOI: 10.1128/iai.00106-11
|View full text |Cite
|
Sign up to set email alerts
|

Sialidase and Sialoglycoproteases Can Modulate Virulence in Porphyromonas gingivalis

Abstract: The Porphyromonas gingivalis recombinant VimA can interact with the gingipains and several other proteins, including a sialidase. Sialylation can be involved in protein maturation; however, its role in virulence regulation in P. gingivalis is unknown. The three sialidase-related proteins in P. gingivalis showed the characteristic sialidase Asp signature motif (SXDXGXTW) and other unique domains. To evaluate the roles of the associated genes, randomly chosen P. gingivalis isogenic mutants created by allelic exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
1
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(83 citation statements)
references
References 59 publications
(70 reference statements)
3
71
1
8
Order By: Relevance
“…Posttranslational modification linked to glycosylation has been shown to be important to the maturation pathway of the gingipains (50). We have also previously shown that sialidase activity may be involved in gingipain activity and other virulence factors in P. gingivalis (51). In our study, the sialidase-encoding gene (PG_0352) was downregulated in P. gingivalis FLL366 (⌬PG_2212), which would be consistent with its role in gingipain biogenesis.…”
Section: Figsupporting
confidence: 74%
“…Posttranslational modification linked to glycosylation has been shown to be important to the maturation pathway of the gingipains (50). We have also previously shown that sialidase activity may be involved in gingipain activity and other virulence factors in P. gingivalis (51). In our study, the sialidase-encoding gene (PG_0352) was downregulated in P. gingivalis FLL366 (⌬PG_2212), which would be consistent with its role in gingipain biogenesis.…”
Section: Figsupporting
confidence: 74%
“…The VimA protein can interact with the sialidase protein from P. gingivalis (2,64). Furthermore, sialidase may be involved in the posttranscriptional regulation of the gingipains (2).…”
Section: Resultsmentioning
confidence: 99%
“…Non-gingipain protease estimation was carried out using a protease assay kit (Molecular Probes) as previously described (2). The presence of Arg-X-and Lys-X-specific gingipain activities was determined as reported elsewhere (34).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations